2012
DOI: 10.1111/j.1471-0374.2012.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnational issue networks in real and virtual space: the case of women, peace and security

Abstract: To what extent do online issue networks serve as a proxy for their real‐space counterparts in structure and substance? This question is significant because a number of scholars have begun to study transnational advocacy networks through their representations online. We explored whether this assumption is valid by comparing the network composition and agenda composition of the advocacy network around ‘women, peace and security’, as operationalized through a web‐based survey of actual activists, and the network'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
21
1
1
Order By: Relevance
“…See also Carpenter and Jose 2012. ideas, assumptions, or discourses advocates across issue networks hold in common: they are "particularly suited to the study of attitudes and experiences around specific topics" and to how those topics are articulated in social settings. This finding suggests the official network agenda as measured by aggregating network websites either reflects or constructs the understandings of individuals who identify themselves closely with a transnational network.…”
Section: Case Selection: the Human Security Networkmentioning
confidence: 99%
“…See also Carpenter and Jose 2012. ideas, assumptions, or discourses advocates across issue networks hold in common: they are "particularly suited to the study of attitudes and experiences around specific topics" and to how those topics are articulated in social settings. This finding suggests the official network agenda as measured by aggregating network websites either reflects or constructs the understandings of individuals who identify themselves closely with a transnational network.…”
Section: Case Selection: the Human Security Networkmentioning
confidence: 99%
“…While some support was offered for the methodological appropriateness of using hyperlink activity to study policy networks, it was also found that the meaning and significance of hyperlinks varied according to context. Previous studies have also found that hyperlink activity may be aspirational in order to legitimate the linking organization by implying an affiliation with a more respected peer organization (Carpenter & Jose, ; Rogers, ).…”
Section: Online Measures Of Collaborative Networkmentioning
confidence: 99%
“… Restricting to this network subset also has the advantage of reducing the risk of incorporating “false positive” nodes. When link‐tracing or other forms of snowball sampling of organizations is incorporated into online network data collection process, there is a risk that nodes with no collaborative ties to organizations in the original survey sample may inadvertently be included in the online network (Carpenter & Jose, ).…”
mentioning
confidence: 99%
“…The importance of the internet for connecting NGOs, activists and governmental actors has become self-evident, particularly with regard to the international communication flows in TANs (Bimber and Davis 2003;McNutt 2006). Scholars increasingly use network analysis tools capable of exploiting available data via webcrawlers and webscrappers (for example, Bae and Choi 2000;Bennett 2003;Carpenter and Jose 2012;Lusher and Ackland 2011). This work is predicated on the notion that the online network mimics the transnational network in structure and content (Bennett 2003;Carpenter and Jose 2012;Park and Thelwall 2003).…”
Section: Hyperlink Analysismentioning
confidence: 99%